2019
DOI: 10.26911/thejmch.2019.04.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Analysis on the Contextual Effect of Posyandu on Exclusive Breastfeeding in Sleman, Yogyakarta

Abstract: Background:There is an increasing evidence that exclusive breastfeeding (EBF) up to six-month of age has important consequences on health and nutritional outcomes of children. However, studies on the contextual effect of integrated halth post (posyandu) on EBF are scarce. The purpose of this study was to examine the contextual effect of posyandu on exclusive breastfeeding using multilevel analysis. Subjects and Method: A cross-sectional study was conducted in Sleman, Yogyakarta, from November to December 2018.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…There is an influence of integrated health post on exclusive breastfeeding. A study by Lestari (2019) showed integrated health post had contextual influence on exclusive breastfeeding. Integrated health post was an increase in the quality of human resources from an early age through social services in the community that support development.…”
Section: The Effect Of Integrated Health Post On Exclusive Breastfeedingmentioning
confidence: 99%
“…There is an influence of integrated health post on exclusive breastfeeding. A study by Lestari (2019) showed integrated health post had contextual influence on exclusive breastfeeding. Integrated health post was an increase in the quality of human resources from an early age through social services in the community that support development.…”
Section: The Effect Of Integrated Health Post On Exclusive Breastfeedingmentioning
confidence: 99%
“…Ibu hamil multipara memiliki pengetahuan dari kehamilan sebelum sebelumnya tertuama terkait dengan pemberian ASI. Ibu multipara memiliki pengalaman dari kehamilan sebelum sebelumnya (Lestari et al, 2019;Wardani et al, 2017;Kitano et al, 2016) 5. Tenaga kesehatan Dukungan menyusui baik dari pemberian informasi dan praktik menyusui oleh tenaga kesehatan atau tenaga berkompeten merupakan hal yang sangat dibutuhkan oleh ibu.…”
Section: Paritasunclassified